Contribution of demand shifts to industrial SO2 emissions in a transition economy: Evidence from China. (15th October 2017) - Jiao, Jianling; Han, Xiaofei; Li, Fangyi; Bai, Yu; Yu, Yadong
Abstract: For the past 20 years, sulfur dioxide (SO2 ) emissions control has been a goal in China whose economy has been characterized as fast growing and in enormous transition. As a prerequisite for effective future SO2 emissions control, a detailed investigation is needed to uncover and assess the contributions to changes in SO2 emissions of key underlying drivers associated with China's evolving demand structure. Using structural decomposition analysis (SDA), considering industrial characteristics and sector interactions, this study identifies the underlying drivers behind China's demand structure shifts as well as their contributions to changes in industrial SO2 emissions. The results show that the change in total final demand was the largest driver of the increase in SO2 emissions, resulting in an increase of 36.64 million tons (Mt) SO2 emissions during the time period 1997 to 2012. From the final demand perspective, the change in capital formation was the largest contributor, resulting in an increase of 16.78 Mt SO2 emissions, and accounting for 45% of the increase due to final demand shifts. The construction industry was the primary trigger of industrial SO2 emissions growth caused by shifts in final demand, with an induced amount (impact on other industries) of SO2 emissions of 10.14 Mt. The key drivers capturing shifts in final demand were mainly capital formation in the construction industry, capital formation and exports in technology-intensive industries, and consumption in the services industries. The recommendation is that to control industrial SO2 emissions, China should depend first on its economic transition that includes technology improvements and industry structure optimization for both final demand and production. Highlights: Economic change has proved to be crucial to mitigate SO2 emissions by technology improvements and demand shifts. Drivers of SO2 emissions are assessed and examined in different industries and time periods. Capital formation in construction is the primary trigger for emissions growth. Growth of investment and exports in technology-intensive industry and consumption in service industry are strong drivers.